(untitled) (INTERNATIONAL JOURNAL OF EDUCATION (IJE), 2024)
Positive education is the fast-growing area of educational research, which is associated with the integration of well-being and academic achievement within the school context. The paper investigates the interplay of positive education implemented through the Happiness Curriculum in schools as a driver to improve life and social skills among students. The present study targeted to measure the impact of the Happiness Curriculum on the well-being of the students, improvement of their emotional intelligence, and increase in good social interaction. The paper also reviews current literature on the impact of positive education on outcomes of students. Some studies did find that when positive affect was increased through school-based interventions that generally increased the level of well-being among the students, increases in student success, performance improvements in achievements, and improvements in behaviour and mental health were the result. Now, the Happiness Curriculum is being rolled out in a few privileged schools, designed with the curriculum of Happiness, Gratitude, and tools of Mindfulness and Empathy. From that, therefore, the thematic analysis of the research articles and case studies carried out on the Happiness Curriculum documents several themes brought about by this program: development of emotional intelligence, increased social connectedness, and promotion of pro-social behaviours. This, therefore, means that the Happiness Curriculum significantly improved social well-being, emotional well-being, and overall happiness among the students. There is, therefore, no overstressing the need to include positive education initiatives, such as the Happiness Curriculum, in the school curriculum, so that students are nurtured in a positive school environment and are able to develop more life skills and social skills. The present study adds to the growing literature on positive education and its potential effects on student well-being and academic performance. This paper, in general, provides valuable insights into the way positive education interplays, and in turn, brings out its effects on student outcomes. Another critical aspect is the way promoting happiness and well-being in schools enhances life skills and social skills among students from a larger perspective.